2016
DOI: 10.3325/cmj.2016.57.566
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in leptin and leptin receptor genes is a risk factor for idiopathic recurrent spontaneous abortion

Abstract: AimTo determine whether maternal leptin (LEP) and leptin receptor (LEPR) gene polymorphisms are associated with idiopathic recurrent spontaneous abortion (IRSA).MethodsThis case-control association study conducted from 2010 to 2012 at the Department of Gynecology and Obstetrics, University Hospital Center Osijek and Clinical Institute of Medical Genetics Ljubljana included 178 women with a history of three or more IRSAs before the 22nd week of gestation and 145 women with at least two live births and no histor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“… did not find a correlation between this polymorphism and recurrent miscarriage. However, other studies have reported that these genetic variants are associated with pregnancy recurrent loss (Table ) .…”
Section: Leptin and Pathologies Associated With Pregnancymentioning
confidence: 99%
“… did not find a correlation between this polymorphism and recurrent miscarriage. However, other studies have reported that these genetic variants are associated with pregnancy recurrent loss (Table ) .…”
Section: Leptin and Pathologies Associated With Pregnancymentioning
confidence: 99%
“…[ 4 ] Certainly, genetic background is widely paid attention by scholars and a number of genes are discovered to be associated with RSA development, such as LEPR , MTHFR , and factor V genes. [ 5 , 6 ] Recently, with the development of molecular techniques, various genetic variants have been confirmed to be associated with RSA occurrence risk.…”
Section: Introductionmentioning
confidence: 99%
“…The association of LEPR gene with pathologies, including obesity [ 20 ], diabetes [ 17 , 22 ], pregnancy complications [ 28 30 ], cancer [ 31 , 32 ] was investigated in several populations. Few studies on Caucasian and Asian populations examined the association of LEPR genetic variants with PCOS, but with inconclusive findings, and an ethnic contribution to this association was suggested.…”
Section: Discussionmentioning
confidence: 99%
“…combination of LEPR pair of SNPs. This was followed by the construction of 3-locus haplotypes by the expectation maximization method, using the default method of Gabriel [28]. Multiple comparisons were corrected for by Bonferroni method, according to: corrected P (Pc) = 1− [1 − P) n ]; n denoting number of comparisons.…”
Section: Haploview 42 Was Used For Determination Of the Extent Of LImentioning
confidence: 99%